The effect of urbanisation on pollinator abundance and reproductive success - Lamb, Ieuan (2022)
Pollinators are the basis of ecosystem services across all land-use types. Current global trends reveal that pollinators and their services are declining due to a variety of anthropogenic threats, including habitat fragmentation, pesticide use, climate change, and parasites and pathogens from commercially reared bees. Wild pollinator declines will increase global food security risks, especially the supply of vital dietary vitamins and micronutrients. Urban areas have been found to provide more improved habitat quality than some rural landscapes and provide refuge from the combination of lethal threats that occur within modern agricultural landscapes. We experimentally tested accessible food resource provision for solitary bees found within landscapes across an urban gradient, by introducing standardised tube nests seeded with Osmia bicornis pupae and measuring the reproductive output of the adults that emerged from those pupae. In addition, pollinator group richness and abundance were surveyed at every nest site. The urban gradient encompassed highly urbanised landscapes, suburban landscapes with increasing green cover, grasslands, and woodlands. Osmia bicornis reproduction was lowest in highly urban sites and highest in natural landscapes. In suburban landscapes reproductive output was lower than natural landscapes but still at sufficient levels to support stable populations. Greenspace within suburban landscapes had a negative impact on reproductive output suggesting habitat quality was higher within residential gardens than suburban parks. Hoverflies and solitary bee populations were associated negatively with urbanisation but bumblebees, Lepidoptera and honey bees were unaffected. This is proposed to be due to differences in mobility and provision of nesting and larval habitats within urban areas.